Proyecto de factibilidad para la creación de una empresa de autocinema en la ciudad de Lago Agrio, provincia de Sucumbíos - Pineda Casanova, Daisy Cristina (2015)
The purpose of this study is to "determine the feasibility of creating a company Drive in the city of Lago Agrio, Sucumbios province"; which it was developed with the use of deductive, inductive, synthetic and statistical methods and with the support of the techniques of observation and survey of a sample of 382 people in the economically active population of Lago Agrio Canton. Among the most significant findings is that the study of market potential demand of 71.99% of the study population, corresponding to 42,419 potential claimants was determined; of which 85.45% corresponding to 36,249 vehicle owners are real plaintiffs who would access the service on average 24 times a year, reaching a total of 869,985 customers; number of which 96.17% were willing to make use of the drive-services, obtaining an effective demand of 836,666 for the first year; in the study of supply it was determined that there are no companies offering similar services so that the supply is zero, so unsatisfied demand is equal to the effective demand. The technical work is to establish an installed capacity of 18,720 customers, estimated to start operations at 80% capacity taking into account factors that may affect the influx of customers, such as technical failures, interruptions for maintenance. The company will be located in the province of Sucumbios Lago Agrio canton, parish Nueva Loja, Progress Avenue and Tahuantinsuyo, most densely populated area in the region. Organic-Functional study establishes that for the proper coordination of the drive-administrative and productive activities, recruitment of 8 people is required, that is, eight new jobs will be created. The law firm, states that the company will be created in the form of Limited Company with the corporate name "Drive-Casanova" Cia. Ltda. In the Economic and Financial study it shows that the investment needed for the implementation of the project is $ 100,016.31; value which will be financed 60% with input from partners and the remaining 40% a loan is processed in the National Development Bank with an interest rate of 10% annually; the unit cost for each client that accesses the service is $ 6.93, which value is added to a profit of 29.99% giving a sales price of $ 9.00; in the Profit and Loss a profit of $ 18,517.34 for the first year and the tenth year of $ 23,742.97 and a cash flow of $ 21,699.77 and for the tenth year of $ 53,283.50 is established. The financial evaluation shows that the company has a range of $ 55,203.22; IRR is equal to 20.50%; the cost-benefit ratio is 1.30 figure shows that for every dollar invested the company earns $ 0.30 cents; retrieves the capital in 4 years, 6 months and 14 days, the indicators are favorable assessment demonstrating that the project implementation is feasible. Given that the results obtained are encouraging it is recommended to implement the company places high liquidity reporting which allows generating employment as well as a new option for wholesome family